FEATURES OF YERSINIA PESTIS BIOFILM FORMATION IN CITELLOPHILUS TESOUORUM ALTAICUS FLEA - L. P. Bazanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Data of the experimental investigation, using typical for the focus virulent Yersinia pestis subsp. pestis strains were analyzed to detect special features of a plague microbe biofilm formation (conglomerates, «blocks») in the main plague carrier, Citellophilus tesquorum altaicus fleas, in Tuva natural focus. It was established that biofilm (bacterial «blocks») played the important role both in plague transmission, by fleas and also in the agent preservation, by these insects. Results of the analysis indicated the prevailing significance of C. tesquorum. altaicus females in plague agent preservation and. explained some mechanisms of its survival in fleas during a cold season in Tuva natural plague focus. Under adverse conditions during the autumn period Y. pestis biofilms («blocks») accumulate mainly in a digestive tract of the main carrier females and. so can survive in fleas for a long time.